Evaluasi Pembelajaran Matematika dengan Pendekatan Saintifik - Isrofil Siregar; M. Kibar; Muhammad Saharudin; Mista Aldi Susanto (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
Education is one of the fields that continuously evolves alongside the rapid advancement of technology. One effort to enhance the quality of education is by implementing a scientific approach in the learning process. This research aims to analyze the contribution of the scientific learning approach to the development of students' self-directed learning at SDN Semper Barat 11, especially in class V. The research method used is descriptive qualitative with data collection techniques through interviews, observations, and documentation. The results show that lesson planning with a scientific approach is well executed, covering the setting of learning objectives, selection of learning models, strategies, learning media, and evaluation. The implementation of learning with a scientific approach in class V is carried out through activities such as observing, questioning, gathering information, reasoning, and communicating. The research also indicates that students experience an improvement in self-directed learning, characterized by active engagement in learning, high motivation, initiative-driven learning, and self-control. Thus, the scientific learning approach significantly contributes to the development of students' self-directed learning at SDN Semper Barat 11. This research provides valuable insights for educational practitioners in designing more effective learning strategies and offers empirical groundwork for enhancing learning methods oriented towards developing students' self-directed learning.